Concomitant Burkholderiapseudomallei and Staphylococcus aureus Infection in a chronic kidney disease patient: A Case Report and Literature Review - Hamid, Norjihan Abdul; Mazlan, Mohd Zulfakar; Salmuna, Zeti Norfidiyati (Bangladesh Journal of Medical Science, 2021)
Melioidosis can happen in humans and animals. It has a wide range of clinical presentations that include asymptomatic infection, ulcers or abscesses of the skin, pneumonia, and multiple internal organ abscesses that may lead to fulminant septic shock. The organism presence in soil and surface of the water. We present a case of a non-diabetic chronic kidney disease patient presented with multiple carbuncles and respiratory melioidosis in which we are able to isolate B. pseudomallei after prolonging the plate incubation for 48-hours. We also suggested available tests in most diagnostic microbiology laboratory for identification of the organism. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.456-458